Analysis of the economic interrelations between human resource training management and innovative entrepreneurship - Tulkin Shokirovich Ergashev (THE INNOVATION ECONOMY, 2026)
The article examines the scientific justification of the economic interrelations between human resource training management and innovative entrepreneurial activity. In particular, based on various economic theories, the priorities of supporting innovative entrepreneurship through human resource training have been identified management